Zakat Literacy Among Indonesian Z Generation: Does Gender Matter? - Masrini, Najmi Laili; Medias, Fahmi; Pambuko, Zulfikar Bagus (Ulul Albab: Jurnal Studi dan Penelitian Hukum Islam, 2023)
Gaps between potential and realization of collection fund ziswaf caused by trust to institution zakat, knowledge about zakat and level of education. Generation Z as a generation that is currently entering productive age and has the potential to be educated to become zakat payers and as a productive group in the field of philanthropy. It is believed that these generation represent a group that is beginning to reach working age and can receive the education required for paying zakat. This research aims to analyze the zakat literacy level of generation Z in Magelang City and Regency. This research was conducted using a quantitative approach. Sample selection was carried out using a purposive sampling technique and a sample of 153 people was obtained through distributing online questionnaires. Hypothesis testing was carried out using quantitative descriptive analysis techniques and independent sample t-test. The research results show that the zakat literacy level of Gen Z is moderate literacy with an average of 75.91. Zakahliteracy is built from two dimensions, namely basic understanding of zakat of 82.01 or high literacy and advanced understanding of zakah of 64.59 or moderate literacy. Furthermore, if we compare the level of zakat literacy based on gender, it is known that there is no significant difference, with a significance value of 0.852, which is greater than 0.05